IMPROVING LITERACY IN THE DIGITAL AGE: UNLEASHING CRITICAL THINKING POTENTIAL - Prasastiningtyas, Widyapuri; Ubaidillah, Ahmad Zulfahmi; Aprianti, Ine; Nurfadilah, Lucy (PT Altin Riset Publishing, 2024)
The study also found that literacy education in schools and families plays an important role in shaping individuals' critical thinking skills. Learning that involves relevant digital media and content tailored to individual needs, as well as approaches that encourage critical reflection and dialogue, can improve literacy in the digital age and critical thinking skills. Theoretical foundations that support the relationship between literacy in the digital age and critical thinking skills are explored to provide a deeper understanding of the role of literacy in the digital age. The research method used is a qualitative approach involving two groups of research subjects, namely high school students and university students. Data collection was conducted through in-depth interviews and surveys to obtain their views and perceptions related to literacy and critical thinking in the digital era. The results showed that increasing literacy in the digital era significantly contributed to the development of critical thinking potential in individuals. Research subjects who have higher literacy levels tend to be better able to critically analyze information, identify fake news, and critically evaluate information sources. They also have a higher awareness of the dangers of misleading information and are better able to sort out relevant information.